HASS PhD graduate careers and knowledge transfer: A conduit for enduring, multi-sector networks. (October 2020) - Barnacle, Robyn; Cuthbert, Denise; Schmidt, Christine; Batty, Craig
Rising worldwide scrutiny of the PhD has focused on issues such as return on investment and career outcomes. This article investigates PhD graduate careers and knowledge transfer looking at the Humanities, Arts and Social Sciences (HASS). Firstly, our extensive literature review of PhD graduate outcomes reveals limited knowledge of HASS careers and a Science, Technology, Engineering and Mathematics (STEM) bias. Secondly, our case study of graduates suggests HASS PhDs provide a vital conduit for end-user engagement and knowledge transfer. Our findings deepen knowledge about the careers of HASS PhDs by revealing pre-existing professional networks may be harnessed to inform end-user relationships throughout candidature and post-graduation. Contrary to dominant assumptions, these networks may endure even for graduates in the academy. This under-recognized phenomenon demonstrates the multi-sector knowledge transfer capacity of HASS researchers with implications for their research capability and career development needs and perceptions of the value of their research.